Extraction and purification of a highly thermostable alkaline caseinolytic protease from wastes Penaeus vannamei suitable for food and detergent industries. (1st July 2016) - Dadshahi, Zahra; Homaei, Ahmad; Zeinali, Farrokhzad; Sajedi, Reza H.; Khajeh, Khosro
Highlights: Novel thermostable protease was purified from wastes Penaeus vannamei . Characterized the purified enzyme for kinetic constants, reaction parameters and substrate specificity. This 24 kDa protease was active in a wide range of pH and temperature. This stability of the enzyme indicates a high potential for industrial applications. Considering production cost and reclamation of waste seems to be a promising approach. Abstract: A novel thermostable protease was purified from Penaeus vannamei from Persian Gulf to homogeneity level using ammonium sulfate precipitation and anion-exchange chromatography. The purified protease showed a single band on native and SDS–PAGE with a molecular weight of 24 kDa on SDS–PAGE. The enzyme showed the broad highest catalytic activity for hydrolysis of the substrate with maximal activity at pH 7 and 80 °C. Activity of the enzyme was inhibited by Hg 2+, Zn 2+ Co 2+ and Cu 2+, while protease activity was increased in the presence of Fe 2+ and Mn 2+ by factors of 173% and 102%, respectively. Enzyme shows a broad substrate specificity and hydrolyzes both natural and synthetic substrates. Based on the Michaelis–Menten plots, the K m with casein as substrate was 16.8 μM and V max was 82.6 μM/min. The enzyme, derived from L. vannamei, possesses unique characteristics and could be used in various industrial and biotechnological applications.